Fungal diversity associated with the decomposition of Avicennia marina leaf litter at various salinity levels (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yunasfi, Susetya IE, Utomo B, Dalimunthe A, Samsuri, Zaitunah A. 2024. Fungal diversity associated with the decomposition of Avicennia marina leaf litter at various salinity levels. Biodiversitas 25: 792-800. The process of litter decomposition in mangrove ecosystem is influenced by both biological and environmental factors. Biological factors include organisms, such as worms, snails, bacteria, and fungi, while environmental factors are soil, water pH, salinity, and others. Therefore, this study aimed to determine the effect of salinity level and length of decomposition period, dominant fungi, as well as carbohydrate and protein levels in Avicennia marina leaf litter. In the experiment, litter bags containing 50 g of A. marina leaf litter were used and placed at salinity levels of
Keywords: Avicennia marina, carbohydrates, decomposition, leaf litter, mangrove, protein, salinity